WHAT IS THE PLACE OF GRAMMAR IN ENGLISH LANGUAGE TEACHING? - Kayumova , Baxtigul Abdirauf qizi (Educational Research in Universal Sciences, 2023)
Before we can think about the place of grammar in the instruction of the English language, we must first understand its function in language. Every language has its own grammar. Language grammar is crucial. Thus, the study of language is the main focus of grammar. It describes the challenges and issues associated with learning a language and directs us toward efficient language use in daily life. Grammar explains how words are created and the rationale for their division into different groups. It also shows us how words are put together and organized into phrases. Grammar helps us become accustomed to sentence form. It allows us to comprehend the structure of phrases and how they are applied in our daily lives for proper and effective communication. Since the dawn of language learning in the annals of humankind, grammar has been the subject of discussion among many educators, researchers, and linguists.